THE ROLE OF THE STATE IN DEVELOPING SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN THE CONTEXT OF A GREEN ECONOMY - Umarov Muzaffar Yusupbayevich; Bazarbayev Murotjon Holmamat o’g’li; Otamurodov Rasulbek Batirovich; Atadjanov Kadambay Sapayevich (Scholar Express Journals, 2025)
This scientific article systematically analyzes the role and functions of the state in developing small business and private entrepreneurship within the context of a green economy. In recent years, the issue of environmental sustainability has risen to the global agenda, intensifying the need to conduct economic activities with environmental responsibility. In this process, the concept of a green economy is becoming increasingly relevant as a means of achieving sustainable development. Small businesses and private entrepreneurship entities, in particular, can become key participants in this economic model due to their flexibility, openness to innovation, and ability to quickly adopt new technologies. The study specifically examines aspects of the state's functions in this area, such as establishing a regulatory framework, developing financial incentives, promoting the implementation of environmental innovations, and setting up coordinating institutions. An in-depth analysis was conducted using analytical, comparative, and empirical methods, based on the strategies, legislative acts, and practical experiences of the Republic of Uzbekistan. The article also identifies existing opportunities and obstacles in the Uzbek context by comparing them with international experiences.
Keywords: green economy; sustainable development; small business